A novel approach in electron beam radiation therapy of lips carcinoma: A Monte Carlo study. Issue 4 (27th March 2013) - Shokrani, Parvaneh; Baradaran‐Ghahfarokhi, Milad; Zadeh, Maryam Khorami
Abstract : Purpose: : Squamous cell carcinoma (SCC) is commonly treated by electron beam radiotherapy (EBRT) followed by a boost via brachytherapy. Considering the limitations associated with brachytherapy, in this study, a novel boosting technique in EBRT of lip carcinoma using an internal shield as an internal dose enhancer tool (IDET) was evaluated. An IDET is referred to a partially covered internal shield located behind the lip. It was intended to show that while the backscattered electrons are absorbed in the portion covered with a low atomic number material, they will enhance the target dose in the uncovered area. Methods: : Monte‐Carlo models of 6 and 8 MeV electron beams were developed using BEAMnrc code and were validated against experimental measurements. Using the developed models, dose distributions in a lip phantom were calculated and the effect of an IDET on target dose enhancement was evaluated. Typical lip thicknesses of 1.5 and 2.0 cm were considered. A 5 × 5 cm 2 of lead covered by 0.5 cm of polystyrene was used as an internal shield, while a 4 × 4 cm 2 uncovered area of the shield was used as the dose enhancer. Results: : Using the IDET, the maximum dose enhancement as a percentage of dose at dmax of the unshielded field was 157.6% and 136.1% for 6 and 8 MeV beams, respectively. The best outcome was achieved for lip thickness of 1.5 cm and target thickness of less than 0.8 cm. For lateral dose coverage of planning target volume, the 80% isodose curve at the lip‐IDET interface showed a 1.2 cm expansion, compared to the unshielded field. Conclusions: : This study showed that a boost concomitant EBRT of lip is possible by modifying an internal shield into an IDET. This boosting method is especially applicable to cases in which brachytherapy faces limitations, such as small thicknesses of lips and targets located at the buccal surface of the lip.